Resonator-based detection in nanorods. (1st September 2017) - Morassi, A.; Fernández-Sáez, J.; Zaera, R.; Loya, J.A.
Highlights: The vibrations of nanoresonators with a single point mass have been addressed. The modified strain gradient theory has been used to account for size effects. Exact and perturbative solutions for the natural frequencies have been obtained. The point mass identification from minimal frequency data has been considered. Abstract: In this paper the axial vibrational behavior of nanorods with an attached point-mass is studied, using the modified strain energy theory. The natural frequencies of the nanorod with the concentrated mass are obtained for different boundary conditions. The effects of the concentrated mass intensity, mass location, as well as the value of scale parameters have been analysed. For the case of small intensity of the concentrated mass, the natural frequencies of the nanorod can be estimated using a first order perturbative solution. These approximate results are compared with those corresponding to the exact solution. For this case, from the properties of the eigenvalue perturbative theory, the identification of single point mass in uniform nanorods (mass intensity and position) is addressed. The results obtained encourage the use of axial vibrations of nanorods as a very precise sensing technique.